Colonization of distant organs by tumor cells generating circulating homotypic clusters adaptive to fluid shear stress - Manabu Maeshiro (Nature Portfolio, 2021)
Abstract Once disseminated tumor cells (DTCs) arrive at a metastatic organ, they remain there, latent, and become seeds of metastasis. However, the clonal composition of DTCs in a latent state remains unclear. Here, we applied high-resolution DNA barcode tracking to a mouse model that recapitulated the metastatic dormancy of head and neck squamous cell carcinoma (HNSCC). We found that clones abundantly circulated peripheral blood dominated DTCs. Through analyses of multiple barcoded clonal lines, we identified specific subclonal population that preferentially generated homotypic circulating tumor cell (CTC) clusters and dominated DTCs. Despite no notable features under static conditions, this population significantly generated stable cell aggregates that were resistant to anoikis under fluid shear stress (FSS) conditions in an E-cadherin-dependent manner. Our data from various cancer cell lines indicated that the ability of aggregate-constituting cells to regulate cortical actin-myosin dynamics governed the aggregates’ stability in FSS. The CTC cluster-originating cells were characterized by the expression of a subset of E-cadherin binding factors enriched with actin cytoskeleton regulators. Furthermore, this expression signature was associated with locoregional and metastatic recurrence in HNSCC patients. These results reveal a biological selection of tumor cells capable of generating FSS-adaptive CTC clusters, which leads to distant colonization.